Evaluation Of Shelf-Life Equation Models Derived From Unidirectional Fick's Law - M Arpah; Rizal Syarief (Jurnal Teknologi dan Industri Pangan, 2000)
The aim of this research was to study the variation of shelf-life values, obtained in quantifying shelf-life of biscuits among models of accelerated storage studies (ASS) from unidirectional Fick'S law. Shelf-life of biscuits is defined as the length of time of a packaged biscuits can be stored before the onset quality change appears.Four models: Heiss-Eichner (1971), Labuza (1983), Rudolph (1986) and Half Value Period or HVP model (Syarief, 1986) were evaluated. These models shared a common basic principle that they were all derived and developed from unidirectional Fick's law. Therefore, each parameter of individual model can be compared to the athers. A semi empirical approach using reaction kinetics through Arrhenius plot was used as a real shelf-life values.Quantification resulted in two categories of shelf-life values, First those which higher than expected value and second, were lower than expected.Parameter evaluation of components of Heiss-Eichner and Labuza models clearly shown less in number than components of Rudolph and HVP models. This led to a conclusion that the more sophisticated models gave higher shelf-life values as compared to the Arhenius model.